External validation of nomograms including MRI features for the prediction of side-specific extraprostatic extension - Heetman, J G; van der Hoeven, E J R J; Rajwa, P; Zattoni, F; Kesch, C; Shariat, S; Dal Moro, F; Novara, G; La Bombara, G; Sattin, F; von Ostau, N; Pötsch, N; et al. (Prostate cancer and prostatic diseases, 2024)
BACKGROUND: Prediction of side-specific extraprostatic extension (EPE) is crucial in selecting patients for nerve-sparing radical prostatectomy (RP). Multiple nomograms, which include magnetic resonance imaging (MRI) information, are available predict side-specific EPE. It is crucial that the accuracy of these nomograms is assessed with external validation to ensure they can be used in clinical practice to support medical decision-making. METHODS: Data of prostate cancer (PCa) patients that underwent robot-assisted RP (RARP) from 2017 to 2021 at four European tertiary referral centers were collected retrospectively. Four previously developed nomograms for the prediction of side-specific EPE were identified and externally validated. Discrimination (area under the curve [AUC]), calibration and net benefit of four nomograms were assessed. To assess the strongest predictor among the MRI features included in all nomograms, we evaluated their association with side-specific EPE using multivariate regression analysis and Akaike Information Criterion (AIC). RESULTS: This study involved 773 patients with a total of 1546 prostate lobes. EPE was found in 338 (22%) lobes. The AUCs of the models predicting EPE ranged from 72.2% (95% CI 69.1-72.3%) (Wibmer) to 75.5% (95% CI 72.5-78.5%) (Nyarangi-Dix). The nomogram with the highest AUC varied across the cohorts. The Soeterik, Nyarangi-Dix, and Martini nomograms demonstrated fair to good calibration for clinically most relevant thresholds between 5 and 30%. In contrast, the Wibmer nomogram showed substantial overestimation of EPE risk for thresholds above 25%. The Nyarangi-Dix nomogram demonstrated a higher net benefit for risk thresholds between 20 and 30% when compared to the other three nomograms. Of all MRI features, the European Society of Urogenital Radiology score and tumor capsule contact length showed the highest AUCs and lowest AIC. CONCLUSION: The Nyarangi-Dix, Martini and Soeterik nomograms resulted in accurate EPE prediction and are therefore suitable to support medical decision-making.
Keywords: nomogramy; roboticky asistované výkony; Male; retrospektivní studie; magnetická rezonanční tomografie; Prostate; prognóza; Robotic Surgical Procedures; Prostatic Neoplasms; Aged; mužské pohlaví; senioři; prostata; prostatektomie; Nomograms; lidé; Humans; nádory prostaty; Prognosis; Prostatectomy; Retrospective Studies; Magnetic Resonance Imaging; lidé středního věku; Middle Aged